The Impact of Inflation, Economic Growth, Health, and Education on Unemployment in Java (2014-2023) - Herdiwiguna, Randi; Fadli, Faishal (Journal of Development Economic and Social Studies, 2025)
This study examines the impact of inflation, economic growth, health, and education on unemployment in Java from 2014 to 2023. Using panel data from six provinces in Java, the research employs a mutiple linear regresion model to analyze the relationship between these variables. The results indicate that economic growth and health have a significant negative impact on unemployment, while education has a significant positive impact. Inflation, however, does not show a significant effect on unemployment. These findings suggest that improving economic growth and health conditions can reduce unemployment, while the mismatch between education and labor market needs may increase unemployment. The study provides insights for policymakers to address unemployment through targeted economic and social policies.